Аналіз впливу об'єктів нафтогазовидобутку на екологічну безпеку Полтавської області - Рикусова, Надія Іванівна; Шестопалов, Олексій Валерійович; Щукіна, Людмила Павлівна (Молодий вчений, 2019)
У статті проведено аналіз причин забруднення навколишнього природного середовища в процесі розробки нафтогазових родовищ. Визначено, що під час спорудження свердловини використовують матеріали та хімічні реагенти різного ступеня екологічної небезпеки. Охарактеризовані основні підприємства, що негативно впливають на довкілля Полтавщини. При оцінюванні екологічної небезпеки процесу буріння свердловин розглянуто властивості бурових стічних вод, та, як основної їх складової, відпрацьованого бурового розчину. За значенням коефіцієнту небезпеки визначено ступінь небезпеки бурового розчину, що використовується на одній з свердловин нафтогазовидобувного підприємства Полтавської області. Проаналізований взаємозв’язок між індексами загальної кількості захворювань і добувної промисловості та розроблення кар’єрів Полтавського регіону.

The article analyzed the causes of the environment pollution during development of oil and gas fields. It is determined that during construction of a well, materials and chemical reagents of various degrees of environmental hazard were used. The main toxic chemical elements that are part of drilling mud were described. The characteristic of the main types of drilling waste was given. The main enterprises, which have a negative influence on the environment of Poltava region, were described. In assessment of the ecological hazard of the well drilling process, the properties of drilling wastewater, as well as its main component, drilled mud, were considered. By the value of hazard ratio, the degree of danger of drilling mud used on one of the wells of the oil and gas industry in Poltava region was determined. Impact of oil and oil products that can get into water reservoirs and suppress the livelihoods of hydrobionts was estimated. The sump and sumpless technologies of drilling of oil and gas wells were described. Defects of the sump drilling method were revealed and the consequences of the chemical substances entering the aquifers with drinking water were described. The most widespread types of diseases in the population of Poltava region in recent years were analyzed. The first identified diseases found in Poltava and the villages of Poltava region were described. The correlation between the indices of the total number of diseases and extractive industry and development of careers in Poltava region was analyzed. It is proposed to use the method of purification of drill wastewater using coagulants and flocculants, as well as regeneration and reuse of the processed drilling mud instead of dumping it in slurry pits with subsequent remediation. The use of technical means for increasing environmental safety was rationalized.
Analysis of influence of oil and gas extraction on the environmental safety of Poltava region
Keywords: бурові стічні води; буріння; видобуток нафти; екологічна небезпека; захворювання; видобуток газу